Direction of Institutions and Bureaucracies of Forest Management Units (FMUs) in Indonesia - Ahmad Maryudi (Jurnal Ilmu Kehutanan)
The establishment of Forest Management Units (FMUs) has been made as one of the top policy priorities by the Ministry of Environment and Forestry. The policy is expected to become a solution for problems regarding to the management of forests in Indonesia, e.g. poor forest governance, tenurial problems, limited capacity in the management of forests. FMU is conceptualized as a forest management agent/ institution at the field. The policy of establishing FMUs is often viewed to add complexities of the current forest administration and management structures. This paper discusses concepts of institutions and bureaucracies of the FMU policy.